Ischemia modified albumin levels in distinguishing NSTEMI patients from non-ischemic controls and correlation with disease severity - Süleyman Özbıçer; Gülhan yüksel Kalkan; Örsan Deniz Urgun; Salim Neşelioğlu; Özcan Erel (Cukurova Medical Journal, 2021)
Purpose: The aim of this study was to investigate the diagnostic value of ischemia modified albumin (IMA) in early non-ST elevation myocardial infarction (NSTEMI) patients diagnosed with high-sensitive cardiac troponin (hs-cTn)assays. Materials and Methods: In the first three hours of symptom onset, one hundred sixty-two patients without cardiovascular disease history admitted to our hospital with NSTEMI were enrolled between March 2018 and August 2019. The patients' IMA levels were compared with IMA levels of randomly selected, age and the sex-matched control group comprised of 61 subjects with normal coronary angiography results. Results: IMA levels of NSTEMI patients were higher than the control group. In receiver operating characteristic (ROC) curve analysis, a value equal or greater than 0.3855 ABSU has an 82% sensitivity and a 99.4% specificity for diagnosing NSTEMI (AUC: 0.962, 95% CI: 0.937 – 0.986,). In addition, ROC curve analysis revealed moderate predictive power for distinguishing three-vessel disease (cut-off value: 0.4290 ABSU, sensitivity 78.4% and specificity 56.3%, AUC: 0.696, 95% CI: 0.616 – 0.776,). IMA levels were positively correlated with Gensini scores of the patient group. Conclusion: Ischemia-modified albumin, when used alone, was very useful in distinguishing NSTEMI from non-ischemic controls. Besides, IMA levels were positively correlated with CAD severity.